Activation of carbon disulfide by a hypersilyl germylene - Ajithkumar, V. S.; Khilari, Nripen; Ghanwat, Pratiksha B.; Venugopal, Geethu; Koley, Debasis; Sen, Sakya S. (Dalton Transactions, 2024)
In this work, the insertion of CS2 into the Ge-Si bond of PhC(NtBu)2Ge-Si(SiMe3)3 (1) has been investigated, resulting in the formation of PhC(NtBu)2Ge-C( 00000000 00000000 00000000 00000000 11111111 00000000 11111111 00000000 00000000 00000000 S)-S-Si(SiMe3)3 (2). Interestingly, the addition of NHC to 2 allows the release of NHCCS2 with concomitant regeneration of 1. Addition of another equivalent of 1 or an analogous hypersilyl silylene, [PhC(NtBu)2Si-Si(SiMe3)3], to 2 led to the formation of compounds with a GeS (3) or a SiS (4) bond. In this work, the insertion of CS2 into the Ge-Si bond of PhC(NtBu)2Ge-Si(SiMe3)3 (1) has been investigated, resulting in the formation of PhC(NtBu)2Ge-C(S)-S-Si(SiMe3)3 (2).